164 Progressive multifocal leukoencephalopathy (PML) following autologous periph- eral blood stem cell transplantation for multiple myeloma. Issue 6 (27th May 2022) - Fernandes, Peter; Bennett, Karina; Storrar, Neill; Johnson, Peter
Abstract : A 67-year-old man presented with unilateral weakness and reduced dexterity four months after autolo- gous peripheral blood stem cell transplantation for multiple myeloma. The weakness progressed over the following months, with accompanying cognitive and sensory symptoms. Brain MRI showed numerous hyper- intense T2 lesions within the subcortical white matter of both cerebral hemispheres suggestive of demy- elination, progressing rapidly on interval imaging. His CSF tested positive for JC virus, diagnostic of PML. This diagnosis was unexpected as the patient did not appear to be significantly immunocompromised and PML is extremely rare in patients with multiple myeloma. Treatment for progressive multifocal leukoen- cephalopathy is via restoring immune function; in our patient no reversible cause of immuno-suppression was present. At the time of our patient's diagnosis no treatments had been shown to be effective against PML in clinical trials. However, in the last year both pembrolizumab and BK virus specific T-cell therapy have demonstrated efficacy against PML in published clinical trials, offering new hope for patients. Clinicians should consider a diagnosis of PML when assessing patients with neurological symptoms and signs following treatment for multiple myeloma and in other haematological conditions, particularly as efficacious treatments can now be given if PML is diagnosed early. peter.fernandes@ed.ac.uk